Síntese e validação de compensadores "antiwindup" para um sistema multivariável de mistura de líquidos - Pereira, Fábio Henrique Busquim (2019)
The main contribution of this work is the application and analysis of linear controllers, along with antiwindup compensators, in a physical system. The considered system is a multivariate process aimed to control the level and temperature of a fluid in a mixing tank by varying the flows of cold and hot liquid. Since the system is nonlinear, two distinct approaches are used. First, a linear and time invariant model is used to generate a controller and an antiwindup compensator also time invariant. The second approach is to model the system as linear and dependent on time-varying parameters and to compute, as a consequence, a controller and a compensator antiwindup also variants in time. The results of theoretical simulations and practical tests allow to validate and verify the influence of antiwindup on the closed-loop control, proving to be effective.